Real-time in vivo optogenetic neuromodulation and multielectrode electrophysiologic recording with NeuroRighter - Laxpati, Nealen G.; Mahmoudi, Babak; Gutekunst, Claire-Anne; Newman, Jonathan P.; Zeller-Townson, Riley; Gross, Robert E. (Frontiers in Neuroengineering, 2014)
Optogenetic channels have greatly expanded neuroscience’s experimental capabilities, enabling precise genetic targeting and manipulation of neuron subpopulations in awake and behaving animals. However, many barriers to entry remain for this technology – including low-cost and effective hardware for combined optical stimulation and electrophysiologic recording. To address this, we adapted the open-source NeuroRighter multichannel electrophysiology platform for use in awake and behaving rodents in both open and closed-loop stimulation experiments. Here, we present these cost-effective adaptations, including commercially available LED light sources; custom-made optical ferrules; 3-D printed ferrule hardware and software to calibrate and standardize output intensity; and modifications to commercially available electrode arrays enabling stimulation proximally and distally to the recording target. We then demonstrate the capabilities and versatility of these adaptations in several open and closed-loop experiments, as well as demonstrate spectrographic methods of analyzing the results, as well as discuss artifacts of stimulation.